POTENTIAL ANALYSIS AND PROJECTION OF HOUSEHOLD HAZARDOUS WASTE (HHW) IN DKI JAKARTA USING A SYSTEM DYNAMICS APPROACH AND ENVIRONMENTAL IMPACT ASSESSMENT WITH THE LIFE CYCLE ASSESSMENT (LCA) METHOD - Dewi Yantini, Wahyu
As the population grows and socio-economic activities increase, waste generation has also escalated. In DKI Jakarta, residents produce an average of 0.7 kg of waste per person per day, which totals approximately 7,800 tones daily, ultimately ending up at the TPST Bantargebang. While organic and inorganic waste dominate the waste stream, household hazardous waste (HHW) is also present at the community level. Household hazardous waste arises from the use of chemical products in everyday household activities, including cleaning agents, personal care items, paints, pesticides, electronics, and other chemical-containing products. A study was conducted involving 240 households categorized into three economic levels: high, middle, and low. The purpose was to identify the types of hazardous waste generated and the current management practices at the source. The findings revealed that households with high, middle, and low economic statuses generated hazardous waste at rates of 0.009 kg, 0.0103 kg, and 0.0098 kg per person per day, respectively. The overall average hazardous waste generation was calculated to be 0.0098 kg per person per day, which equates to approximately 0.044 liters per person per day. Waste generation projections have been determined using a straightforward dynamic system that comprises two primary subsystems: the population subsystem of DKI Jakarta and the household hazardous waste subsystem. The population subsystem is influenced by both the number and growth rate of the population, while the household hazardous waste generation subsystem is affected by various factors including the city's growth rate (encompassing population, industry, agriculture, and income levels) and the growth rate of household hazardous waste. According to simulation results derived from the Stella model version 9.0.2, household hazardous waste generation in DKI Jakarta is anticipated to reach 49,775,51 tons by 2044. The primary contributors to this waste include the packaging of personal care and beauty products (31.22%), residual packaging of medicines (23.33%), and packaging of cleaning and home maintenance products (23.27%). Among the waste generated, 39.32% are characterized as infectious, followed by 35.63% classified as toxic. The household hazardous waste collection rate has been only 0.2%. So that the development of management is carried out through 3 (three) scenarios with reduction and handling targets by regional policies, namely pessimistic, moderate, and optimistic scenarios. The pessimistic scenario developed a waste reduction of 30% and waste handling of 70% in 2030 through a pattern of segregated waste collection in waste banks and mixed waste in TPS/TPS3R. The moderate scenario targets 30% waste reduction and 70% waste management by 2025 through mixed waste collection at TPS/TPS3R and segregated waste collection at waste banks and RW pick-up points. The optimistic scenario targets a 30% reduction and 70% handling in 2025 with mandatory segregated collection at waste banks and RW pick-up points. Each scenario includes a direct pick-up pattern for e-waste. All three scenarios were developed to achieve 100% collection at sub-district and city-scale FPSS for transport to hazardous waste managers. Potential environmental impacts were analyzed using the Life Cycle Assessment (LCA) method for the management scenarios. The inventory and impact assessment utilized the ecoinvent 37 database, LCIA 2.0.2, and ELCD 3.2. The impact assessment uses the CML-IA Baseline method and normalization and weighting using the World 2002 method. The LCA results show that the optimistic scenario produces the least impact assessment compared to other scenarios. The impact magnitude of the optimistic scenario consists of global warming (GWP 100a) (1.59E+05 kg CO2eq), acidification (6.00E+02 kg SO2 eq), eutrophication (3.59E+02 kg PO43- eq) and human toxicity (1.79E+03 kg 1.4-DB eq). These impacts are 9,1% less than the moderate scenario. In addition, potential health impacts were analyzed through a literature review based on the characteristics of each type of hazardous waste.